Langmuir-Blodgett films incorporating an ionic europium complex - Adati, Renata Danielle [UNESP]; Lima, S. A. M. [UNESP]; Davolos, Marian Rosaly [UNESP]; Jafelicci, M. [UNESP] (Elsevier B.V. Sa, 2009)
Langmuir-Blodgett (LB) technique is a powerful tool to fabricate ultrathin films with highly ordered structures and controllable molecular array for efficient energy and electron transfer, allowing the construction of devices at molecular level. One method to obtain LB films consists in the mixture of classical film-forming molecules, for example Stearic Acid (SA) and functional metal complex. In this work NH(4)[Eu(bmdm)(4)], where the organic ligand bmdm is (butyl methoxy-dibenzoyl-methane) or (1-(4-methoxyphenyl)-3-(4-tert-butylphenyl)propane-1,3-dione) was used to build up Langmuir and LB films. Langmuir isotherms were obtained from (i) NH(4)[Eu(bmdm)(4)] complex and (ii) NH(4)[Eu(bmdm)(4)]/SA (1:1). Results indicated that (i) form multilayer structure; however the surface pressure was insufficient to obtain LB films, and (ii) can easily reproduce and build LB films. The dependence of number of layers in the UV absorption spectra suggest that the complex did not hydrolyze or show decomposition, UV spectral differences observed between the solution and the LB film indicate that the complex has a highly ordered arrangement in the film and the complex has an interaction with SA. Excitation spectra confirm a ligand-europium energy transfer mechanism. The transition lines of Eu(3+) ion were observed in emission spectra of all films, the photoluminescence spectra indicate a fluorescence enhanced effect with the number of LB layers. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Phosphor; Chemical synthesis; Electronic states; Light absorption; Luminescence